ANALISA TINGKAT KECERDASAN AKUNTAN PADA PEMERINTAH DAERAH KOTA SUKABUMI - Gatot Wahyu Nugroho; Ismet Ismatullah (Jurnal Akuntansi Muhammadiyah (JAM), 2019)
Human resources are an important factor for the creation of quality financial reports. The success of an entity can be influenced by the intelligence of human resources. This study aims to determine how much influence the intelligence possessed by a person to the quality of financial statements. Indepedent variables used in this study are intellectual intelligence, emotional intelligence, spiritual intelligence and physical intelligence and the dependent variable is the quality of financial statements. The sample used was 84 respondents, namely the finance department employees in the Sukabumi City Regional Government. Primary data was obtained by distributing questionnaires and the results were tested using statistical test tools. The results of the study show that (1) intellectual intelligence influences the quality of financial statements significantly; (2) emotional intelligence significantly affects the quality of financial statements; (3) spiritual intelligence influences the quality of financial statements significantly; (4) physical intelligence does not affect the quality of financial statements; and together the level of intelligence accountants affect the quality of financial statements with the value of determination coefficient of 96.5% and the remaining 30.5% influenced by other variables.